Preparation and characterization of ceramic nanocomposites in the PZT-BT system - Wanwilai Chaisan (2018)
Nanocomposites of the (1 - x)PZT-xBT system were fabricated by the bimodal particle concept. The effect of fabricating conditions on structural characteristics and dielectric properties of the ceramics was investigated using XRD, SEM, and a standard dielectric measurement. The ceramic-solid solutions and -nanocomposites in the PZT-BT system were comparatively explored. It was clearly seen that the microstructures and the dielectric properties of PZT-BT ceramic-nanocomposites are totally different from those of ceramic-solid solutions. The dielectric behavior of ceramic-nanocomposites displayed superimposition of two phase transitions with a lower maximum value of the dielectric constant than that of the solid solutions. © 2008 Elsevier Ltd and Techna Group S.r.l.